Discovery of NVP‐LEQ506, a Second‐Generation Inhibitor of Smoothened. Issue 8 (2nd July 2013) - Peukert, Stefan; He, Feng; Dai, Miao; Zhang, Rui; Sun, Yingchuan; Miller‐Moslin, Karen; McEwan, Michael; Lagu, Bharat; Wang, Kate; Yusuff, Naeem; Bourret, Aaron; Ramamurthy, Arun; et al.
<x xml:space="preserve">Abstract</x> First disclosure: Continued optimization provided a novel type of Smoothened (Smo) antagonist based on a pyridazine core. The compound, NVP‐LEQ506, currently in phase I clinical trials, combines high intrinsic potency and good pharmacokinetic properties resulting in excellent efficacy in rodent tumor models of medulloblastoma. Activity against a Smo mutant conferring resistance observed in a previous clinical trial with a competitor compound suggests additional therapeutic potential.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>